2016
DOI: 10.1186/s12879-016-1520-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of multiple interventions on HIV incidence in a hyperendemic region in Western Kenya: a modelling study

Abstract: BackgroundMultiple prevention interventions, including early antiretroviral therapy initiation, may reduce HIV incidence in hyperendemic settings. Our aim was to predict the short-term impact of various single and combined interventions on HIV spreading in the adult population of Ndhiwa subcounty (Nyanza Province, Kenya).MethodsA mathematical model was used with data on adults (15–59 years) from the Ndhiwa HIV Impact in Population Survey to compare the impacts on HIV prevalence, HIV incidence rate, and populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Another modelling study [6] investigating the introduction of PrEP among women in Western Kenya found that it could have a substantial impact on incidence (22–28% reduction over four years) if implemented alone and that in combination with increased voluntary medical male circumcision and the implementation of 2013 WHO ART guidelines it could reduce incidence by 46–67%, but cost-effectiveness was not evaluated. Cremin and Hallet [7] used Nyanza, Kenya, as a case study to investigate PrEP intervention efficiencies associated with longer residual protection and changes in cost, adherence and prioritization as a function of coverage and time.…”
Section: Discussionmentioning
confidence: 99%
“…Another modelling study [6] investigating the introduction of PrEP among women in Western Kenya found that it could have a substantial impact on incidence (22–28% reduction over four years) if implemented alone and that in combination with increased voluntary medical male circumcision and the implementation of 2013 WHO ART guidelines it could reduce incidence by 46–67%, but cost-effectiveness was not evaluated. Cremin and Hallet [7] used Nyanza, Kenya, as a case study to investigate PrEP intervention efficiencies associated with longer residual protection and changes in cost, adherence and prioritization as a function of coverage and time.…”
Section: Discussionmentioning
confidence: 99%
“…Kenya, along with other sub-Saharan African countries, has made tremendous strides in the delivery of antiretroviral therapy (ART) to HIV-infected persons (Blaizot et al, 2016; Kelly & Wilson, 2015; Odhiambo, Kellogg, & Kim, 2014). ART coverage in Kenya increased from 64% in 2008 to 80% in 2013 (NACC, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ART coverage increased from 22.0% ( n = 7766) in 2009, to 55.7% ( n = 20 139) in 2014 (study data), and to 82.7% in 2016 . ART coverage was similar for both gender in 2011 (men: 36.7%; women: 35.6%) , but point estimates tended to be higher for women in 2016 (men: 79.1%; women: 84.1%) . During the first year of TB decline in 2010, ART coverage was between 22.0% and 29.9%.…”
Section: Resultsmentioning
confidence: 92%
“…To obtain stratified denominators of PLHIV, sex‐ and age‐stratified population data were multiplied by the corresponding regional HIV prevalence estimates. Because regional stratified HIV prevalence estimates were not available from a single source, we used the 2011 Swaziland HIV Incidence Measurement Survey (SHIMS) estimates for the 20‐ to 49‐year‐olds, the 2006–2007 Demographic and Health Survey (DHS) estimates for the ≤14‐ and ≥50‐year‐olds, and averaged SHIMS and DHS prevalence estimates for the 15‐ to 19‐year‐olds. Finally, the stratified mid‐year numbers of patients active on ART were divided by the corresponding stratified population estimates of PLHIV to obtain sex‐ and age‐stratified ART coverage estimates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation